SOME ASPECTS OF DEVELOPING THE PROFESSIONAL GRAPHIC CREATIVITY OF THE FUTURE ENGINEER - Шомирзаев Махматмурод Хурамович (Journal Park Publishing, 2024)
The article describes the issue of increasing the effectiveness of the educational process by developing the professional-graphic creativity of future engineers based on a competent approach in higher education institutions.
Keywords: student, education, training, competent, approach, future, professional, engineer, design, competence, intellectual, integration, intellectual, creative, cognitive, future, ability, science, craft, efficiency.